IMPLEMENTATION OF QIM BASED AUDIO WATERMARKING USING HYBRID TRANSFORM OF SWT-DCT-SVD METHODS OPTIMIZED WITH GENETIC ALORITHM - Ryan Aminullah; Gelar Budiman; Irma Safitri (TEKTRIKA, 2017)
Nowadays, almost all data transaction is done through the internet because it is easy and could be accessed anywhere. The file is uploaded directly without any security or scanning making people able to upload illegal files or files that is not owned by them. This violation of copyright becomes a huge problem as it reduces the owner’s profit. That is why watermarking method is created. Watermarking is a method of embedding secret information to a host data. The information could be embedded into an audio, image or video data. This research will design an audio watermarking by combining 3 methods of transformation: Stationary Wavelet Transform (SWT), Discrete Cosine Transform (DCT), and Singular Value Decomposition (SVD). SWT separates data’s frequency into high and low. After that, DCT maps correlated high frequency data into uncorrelated coefficient. Then those coefficients will be deconstructed into three matrices u, s, and v using SVD method. Later, the s matric will be embedded with the watermark. With these methods, watermarked audio produce SNR>20dB and BER≈0,1170 in average.